Revitalisasi Koperasi dengan Pemanfaataan Teknologi Informasi Akuntansi pada Koperasi Batik Pati Danowati - Mukhamad Nurkamid; Sri Mulyani; Budi Gunawan (IKIP PGRI Bojonegoro, 2019)
ABSTRACTCooperative revitalization is empowering and reviving cooperatives that are already running but weakening. Bakaran Village Pati district has a unique creative industrial product, namely batik. Local people call this batik with the batik name